Seismic performance evaluation of a 34-story steel building retrofitted with response modification elements. - Weng, Yuan-Tao (Earthquake engineering & structural dynamics.)
The original structural design of this case study consisted of five basement floors and a 34-story hotel tower in Kaohsiung, Taiwan. The construction started in 1993, and the erection of the entire steel frame and the pouring of concrete slabs up to the 26th floor were completed before 1996. However, construction of the original hotel was subsequently suspended for 10 years. Recently, this building has been retrofitted for residential purposes. Buckling restrained braces (BRBs) and eccentrically braced frames were incorporated into the seismic design of the new residential tower. This paper presents the seismic resisting structural system, seismic design criteria, full-scale test results of one BRB member and the as-built welded moment connections. Test results confirm that the two side web-plate stiffening details can effectively improve the rotational capacity of welded moment connection. The paper also discusses the analytical models for simulating the experimental responses of the BRB members and the welded moment connections. Nonlinear response history analyses (NLRHA) indicate that the inelastic deformational demands of the original and the redesigned structures induced by the maximum considered earthquakes are less than those found in the seismic building codes or laboratory tests. This paper also proposes a ground motion scaling method considering multi-mode effects for NLRHA of the example building. It is shown that the proposed scaling method worked well in reducing the scatter in estimated peak seismic demands.